2020
DOI: 10.2478/acve-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Casein Gene Polymorphism in Serbian Holstein-Friesian Cows and Its Relationship with Milk Production Traits

Abstract: The most common types of beta-casein in cow’s milk are A1 and A2, which differ in one amino acid. During the gastrointestinal proteolysis of A1 beta-casein in humans this difference results in the release of beta-casomorphin-7, an opioid which may lead to severe effects on human health, causing various ailments (type-1 diabetes mellitus, ischemic heart disease, arteriosclerosis, sudden infant death syndrome, autism, schizophrenia, gastrointestinal digestive discomfort, as well as increased gastrointestinal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
1
1
0
1
Order By: Relevance
“…However, the average values in this study correspond to those reported in the works of scientists [1,28]. Higher percentages of the main components of cheese (content of protein and fat, dry matter) are shown in the work of scientists [29].…”
Section: Discussion Of Results Of Determining the Dependence Of The C...supporting
confidence: 83%
“…However, the average values in this study correspond to those reported in the works of scientists [1,28]. Higher percentages of the main components of cheese (content of protein and fat, dry matter) are shown in the work of scientists [29].…”
Section: Discussion Of Results Of Determining the Dependence Of The C...supporting
confidence: 83%
“…These results are in line with a previous literature that indicated a negative relation of allele A2 on milk fat content but a positive relation on milk protein content. Although Ristanić et al, (2020) reported a positive relation of allele A2 on both milk protein and milk fat. The highest percentage of A1 variant observed in the Girolando breed in our study could partly be the result of mating of individuals that are closely related genetically.…”
Section: Discussionmentioning
confidence: 92%
“…The Holstein-Friesian (HF) is the leading dairy breed in the world; its genetic potential for high milk yields is being exploited in virtually all developed countries. Milk production and milk composition are the most carefully selected traits in dairy cattle breeding programs [1,2]. The discovery of molecular markers associated with the aforementioned traits and the application of marker-assisted selection (MAS) made a huge impact on dairy cattle breeding in recent decades.…”
Section: Introductionmentioning
confidence: 99%